Analisis Kepuasan Pengguna Aplikasi Kehadiran Panda menggunakan Metode System Usability Scale (Studi Kasus: PT. Puskomedia Indonesia Kreatif) - Aulia Shafira Tri Damayanti; Ika Romadoni Yunita; Pungkas Subarkah (Jurnal Teknologi Informasi dan Multimedia, 2025)
PT Puskomedia Indonesia Kreatif has developed the Panda Attendance Application, a digital technology system for village administration with a focus on the smooth flow of employee infor-mation. This application utilizes QR codes and GPS technology for the attendance or absence of village employees at registered coordinates. One of the issues at PT Puskomedia is that village operators face challenges such as needing to contact the PT Puskomedia system operator for manual attendance tracking, leading to a decline in users. Currently, there are various challenges in the use of the Panda Attendance Application by village government institutions. Several com-plaints have been raised by users regarding technical issues and unsatisfactory user experience. The purpose of this study is to evaluate the level of user acceptance of the Panda application. The method used to analyze user satisfaction is the System Usability Scale (SUS) method. The results of this study yielded a SUS score of 46.22, indicating a low category (Grade E), with a percentile rank of 10%, and classified as poor (Grade E). The nature (adjective) of the application falls into the “Poor” category, and the score of 46.22 places the application in the “Not Acceptable” catego-ry according to the level of acceptance. Recommendations for improvement from this analysis in-clude enhancing system stability and technical improvements such as accelerating the QR code reading process. Responding to user feedback and implementing these improvements is expected to enable the Panda attendance application to achieve a higher level of usability and gain better acceptance from users.